Keabsahan Jual Beli Tanah dan Perlindungan Hukum Pemegang Sertifikat terhadap Penguasaan Tanpa Hak: Analisis Putusan Nomor 4/Pdt.G/2023/PN Boyolali - Habib Dian Fahriza; Evelyn Nawang Cahya; Fadly Ardika Arofa; Gilberth Bonea Rachmat Santoso; Nirvan Wandaniel Manik; Puspaningrum Puspaningrum (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
. Land ownership disputes in Indonesia often involve unauthorized occupation of land by parties lacking a valid legal basis, creating challenges for courts in assessing transaction validity and the evidentiary strength of ownership certificates. This study examines three legal issues in Decision No. 4/Pdt.G/2023/PN Boyolali: the validity of a land sale and purchase transaction before a Land Deed Official (PPAT), the evidentiary strength of Certificate of Ownership No. 01276, and the classification of the defendants’ conduct as an unlawful act under Article 1365 of the Civil Code. This research employs a normative juridical method with a case study approach using primary legal materials, including court decisions and statutory regulations, supported by secondary doctrinal sources. The analysis shows that the transaction before the PPAT fulfilled the requirements of Articles 1457–1458 of the Civil Code as well as customary law principles of transparency (terang) and immediate payment (tunai), thereby establishing its legal validity. The ownership certificate also served as strong documentary evidence under Article 32(1) of Government Regulation No. 24 of 1997, while the defendants failed to present authenticated evidence to support their claims. Moreover, the defendants’ continued occupation of the disputed land without lawful basis and despite repeated demands to vacate satisfied the elements of an unlawful act. This research contributes an integrated analytical framework combining transaction validity, certificate evidentiary strength, and unlawful act doctrine in Indonesian land law.